New insight into the finance-energy nexus: Disaggregated evidence from Turkish sectors - Mert Topcu; Bulent Altay (International Journal of Financial Studies, 2017)
Seeing that reshaped energy economics literature has adopted some new variables in energy demand function, the number of papers looking into the relationship between financial development and energy consumption at the aggregate level has been increasing over the last few years. This paper, however, proposes a new framework using disaggregated data and investigates the nexus between financial development and sectoral energy consumption in Turkey. To this end, panel time series regression and causality techniques are adopted over the period 1989-2011. Empirical results confirm that financial development does have a significant impact on energy consumption, even with disaggregated data. It is also proved that the magnitude of financial development is larger in energy-intensive industries than in less energy-intensive ones.
Keywords: C23; G20; Q43; 330; financial development; energy consumption; Turkey